Design of an MPPT Controller on Boost Converter for for Improving PV Charging Efficiency under Variable Irradiance of PV Modules - Erlillah Rizqi Kusuma Pradani; Delila Cahya Permatasari; Irfin Sandra Asti; Muhammad Imbarothur Mowaviq (Universitas Islam Raden Rahmat, Malang, 2025)
The Photovoltaic (PV) system is a promising renewable energy technology that converts solar radiation into electrical energy through solar cells integrated into solar panels. This study presents the design and implementation of a PV system incorporating a DC–DC boost converter and a Perturb and Observe (P&O)-based Maximum Power Point Tracking (MPPT) algorithm to enhance power conversion efficiency under varying solar irradiance and temperature conditions. The proposed system consists of solar panels, a boost converter–based charge controller, an inverter, and a battery bank as the energy storage unit. The P&O algorithm dynamically adjusts the duty cycle of the boost converter to ensure that the PV array operates at its optimal power point. Experimental results show that the boost converter effectively regulates an input voltage range of 8–13 V to produce a stable output of 12–13.5 V. The system achieves a charging efficiency improvement of 18.6% compared to direct charging without MPPT and reduces the battery charging time by approximately 25%, enabling a 12 V, 6 Ah battery to reach full charge in about 8 hours. The integration of the P&O-based MPPT with the DC–DC boost converter significantly enhances charging efficiency and system reliability. These results demonstrate the effectiveness of the proposed PV system in maximizing power extraction and promoting sustainable energy utilization.